2012
DOI: 10.1055/s-0032-1323721
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Protocol to Assess Arm Swimming Power in Front Crawl

Abstract: Mechanical power output is a reliable predictor of swim speed in front crawl. However, a complete power curve (power vs. load) has not been described for swimming, and intra-cycle power has not been assessed. The purpose of this study was to examine intra-cycle power output at propulsive phases and to determine maximum swimming power, the corresponding load and swimming speed. 18 swimmers (age 22.10±4.31years, height 1.79±0.07 m, arm span 1.85±0.08 m and body mass 76.74±9.00 kg) performed a swim power test. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 26 publications
5
41
0
2
Order By: Relevance
“…The influence of force production on swimming performance has long been discussed (33) and suggests that the force exerted in water is a major factor for success (2,10). For that reason, the magnitude of these forces has been the topic of many studies, although the complexity of the aquatic environment makes its assessment challenging (1).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of force production on swimming performance has long been discussed (33) and suggests that the force exerted in water is a major factor for success (2,10). For that reason, the magnitude of these forces has been the topic of many studies, although the complexity of the aquatic environment makes its assessment challenging (1).…”
Section: Introductionmentioning
confidence: 99%
“…The test consisted in 15 m all-out front-crawl swims across the pool while pulling a different load during each trial, besides the reliability of the test has been shown in previous studies to be very high (Intra-class Correlation Coefficient >0.80) as shown by Dominguez-Castells et al 24 . After a standardized 800 m warm-up, the test started with a load of 45 N. The load increased by 25 N for each trial.…”
Section: Maximal Mechanical External Power Testmentioning
confidence: 91%
“…The protocol ended when the swimmer was not able to complete a trial. Data related to the first and last 2.5 m was discarded to consider only constant speed conditions 24 . The MMEP parameters of interest were acquired by means of a dedicated custom ergometer designed and built by Tecnologicamente S.r.l.…”
Section: Maximal Mechanical External Power Testmentioning
confidence: 99%
“…Dominguez-Castells, Izquierdo, y Arellano (2013), señalan que la potencia generada por el nadador es un predictor fiable de la velocidad de nado al estilo crol. Además, apuntan que la máxima potencia de nado generada guarda una relación lineal con la máxima velocidad de nado, con independencia de la fatiga o del nivel técnico (Seifert, Toussaint, Alberty, Schnitzler y Chollet, 2010 y Toussaint, Carol, Kranenborg y Truijens; citados por Dominguez-Castells, Izquierdo y Arellano, 2013). De hecho, los nadadores de nivel mundial producen mayores picos de potencia que los de menor nivel (Barbosa, Morais, Marques, Costa y Marinho, 2014).…”
Section: Fuerza-explosivaunclassified
“…Un ejemplo en el que se mide la potencia de nado en el agua utilizando esta metodología, lo encontramos en el test que proponen Domínguez-Castells, Izquierdo y Arellano (2013). El objetivo de dicho test será examinar la potencia intra-ciclo en las fases propulsivas y determinar tanto la potencia máxima de nado como la velocidad a la que se alcanza dicha potencia.…”
Section: Valoración De La Fuerza-explosivaunclassified